S-doped graphite carbon nitride material with N defect as well as preparation method and application of S-doped graphite carbon nitride material
By introducing sulfur doping and nitrogen defects into graphite carbon nitride, a bifunctional S-doped graphite carbon nitride material (SCN-E) was prepared, which solved the light absorption rate of existing photocatalysts in photocatalytic reactions. The problem of low and insufficient reactive sites has achieved the effect of efficient degradation of tetracycline antibiotics and efficient production of H2O2.
Patent Information
- Application Number
- CN202510070552.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing graphite carbon nitride photocatalysts have problems such as low light absorption, insufficient reactive sites and high photocarrier recombination rate in photocatalytic reactions, making it difficult to effectively degrade tetracycline antibiotics and efficiently produce H2O2.
By introducing sulfur doping and nitrogen defects into graphite carbon nitride, a bifunctional S-doped graphite carbon nitride material (SCN-E) was prepared by hydrothermal method and secondary calcination method, which improved Photocatalytic properties of materials.
The material can produce 1183.54 μmol·L-1 of H2O2 within 60 minutes of photocatalysis, and achieve a 100% degradation rate of tetracycline antibiotic solution within 30 minutes, and has the stability and efficiency of multiple cycles.
Smart Images

Figure CN119456052A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalysis, and in particular to an S-doped graphite carbon nitride material with N defects, and a preparation method and application thereof. Background Art
[0002] With the continuous innovation and development of science and technology, the problems of energy shortage and environmental pollution have become increasingly prominent. 2 O 2 ) is a multifunctional green oxidant, which is widely used in many fields such as medicine, chemical industry and environmental remediation. In terms of environmental pollution, water pollution caused by antibiotics will pose a serious threat to humans and ecosystems, especially water pollution caused by tetracycline antibiotics will produce drug-resistant bacteria and drug-resistant genes in the water, and the harm caused should not be underestimated.
[0003] Photocatalytic technology replaces the anthraquinone process that has pollution and explosion risks. It uses clean and renewable solar energy to induce the separation of electron-hole pairs on the surface of the photocatalyst to carry out redox reactions. Under the irradiation of sunlight, only water and oxygen (O 2 ) can produce H 2 O 2 In the presence of photocatalysts, photocatalytic technology can effectively use solar energy to remove tetracycline antibiotic solutions in water, and has a good degradation effect in different water matrices. 3 N 4 ) is considered an excellent semiconductor photocatalyst due to its stable physical and chemical properties and suitable energy band structure. However, the original graphite carbon nitride still needs to be modified to improve its light absorption rate, increase the reaction active sites and reduce the recombination of photogenerated carriers. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, the present invention prepares a sulfur (S)-doped gC with nitrogen (N) defects. 3 N 4 The photocatalyst can produce up to 1183.54 μmol·L -1 H 2 O 2 , within 30 min, 5 mg·L -1 Tetracycline hydrochloride (TC) solution, 10 mg·L -1 Oxytetracycline (OTC) solution and 10 mg·L -1 The degradation rates of chlortetracycline (CTC) solution in the reaction mixture were 100%, 92.2% and 93.8%, respectively, and multiple cycles were performed to efficiently produce H.2 O 2 and highly efficient degradation of tetracycline antibiotic solutions.
[0005] The S-doped graphite carbon nitride material with N defects of the present invention has dual functionality. On the one hand, it can photocatalytically degrade tetracycline antibiotic solutions, and on the other hand, it can photocatalytically generate H 2 O 2 The dual functionality of this invention enables it to both synthesize green energy organically under a photocatalytic system and treat antibiotic pollution in the water environment, showing great application potential in both environmental governance and clean energy fields.
[0006] To achieve the above object, the present invention provides the following technical solutions: A S-doped graphite carbon nitride material with N defects, wherein the graphite carbon nitride material can photocatalytically degrade tetracycline antibiotic solution on the one hand, and can photocatalytically generate H on the other hand. 2 O 2 The graphite carbon nitride material produced 1183.54 μmol·L -1 H 2 O 2 , within 30 min, 5 mg·L -1 Tetracycline hydrochloride solution, 10 mg·L -1 of oxytetracycline solution and 10 mg·L -1 The degradation rates of chlortetracycline solution were 100%, 92.2% and 93.8% respectively, and it can be recycled multiple times to efficiently produce H 2 O 2 and highly efficient degradation of tetracycline antibiotic solutions.
[0007] The present invention provides a method for preparing the above-mentioned S-doped graphite carbon nitride material with N defects, wherein melamine is calcined at high temperature in air to prepare original graphite carbon nitride, sublimated sulfur powder is added to the original graphite carbon nitride and mixed, and then the S-doped graphite carbon nitride material with N defects is prepared through a hydrothermal method and a secondary calcination method.
[0008] Further, the following steps are included: (1) Preparation of CN-E: 15 g of melamine was calcined at 520 °C in air at a heating rate of 10 °C / min for 4 h, and then calcined again at 580 °C in air at the same heating rate for 4 h to form the original graphite phase carbon nitride CN-E.
[0009] (2) Preparation of SCN-E: 0.4 g of CN-E and 3.5 g of sublimated sulfur powder were added to 50 ml of deionized water, and the mixture was stirred continuously for 1 h in a water bath at 60 °C. After stirring, the mixture was mixed evenly, and then heated at 180 °C for 12 h to obtain a yellow solid material. The yellow solid material was then washed alternately with ethanol and water for 3 times, and dried to obtain a light yellow block material. The light yellow block material was calcined at 520 °C in nitrogen at a heating rate of 10 °C / min for 2 h to obtain a light yellow powder material SCN-E polymer, i.e., the S-doped graphite carbon nitride material with N defects.
[0010] The present invention also provides a bifunctional photocatalyst, which is prepared by the above method. In the photocatalytic system, a certain amount of the S-doped graphite carbon nitride material with N defects is placed in 50 ml of tetracycline antibiotic aqueous solution and 50 ml of methanol aqueous solution, respectively, to achieve photocatalytic degradation of tetracycline antibiotics and photocatalytic production of H 2 O 2 .
[0011] Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with other S-doped graphitic carbon nitride photocatalytic systems, the present invention has the advantages of high efficiency in degrading tetracycline antibiotics and producing H 2 O 2 The dual functions of this system provide a new idea for combining the use of solar energy to degrade antibiotics in water and generate value-added clean energy.
[0012] (2) The S-doped graphitic carbon nitride material (SCN-E) with N defects prepared in the present invention can be recycled to achieve stable and efficient photocatalytic degradation of tetracycline antibiotics and production of H 2 O 2 effect.
[0013] (3) The S-doped graphite carbon nitride material (SCN-E) with N defects prepared in the present invention can still have a high degradation rate for tetracycline antibiotics in a variety of water matrices. The impurities in different water matrices have little effect on the degradation effect. The SCN-E polymer has good anti-interference ability to impurities in different water matrices during photocatalytic degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a comparison of the degradation effects of the prepared SCN-E polymer and the original graphite phase carbon nitride (CN-E) on tetracycline hydrochloride (TC) under simulated sunlight; Figure 2This is a comparison of the degradation effects of the prepared SCN-E polymer and the original graphite phase carbon nitride (CN-E) on oxytetracycline (OTC) under simulated sunlight; Figure 3 This is a comparison of the degradation effects of the prepared SCN-E polymer and the original graphite phase carbon nitride (CN-E) on chlortetracycline (CTC) under simulated sunlight; Figure 4 It is the cyclic degradation diagram of tetracycline hydrochloride (TC) by the prepared SCN-E polymer under simulated sunlight irradiation; Figure 5 It is the cyclic degradation diagram of oxytetracycline (OTC) by the prepared SCN-E polymer under simulated sunlight irradiation; Figure 6 It is the cyclic degradation diagram of the prepared SCN-E polymer to chlortetracycline (CTC) under simulated sunlight irradiation; Figure 7 This is a comparison chart of the degradation effect of the prepared SCN-E polymer on tetracycline hydrochloride (TC) in different water matrices under simulated sunlight irradiation; Figure 8 This is a comparison chart of the degradation effect of the prepared SCN-E polymer on oxytetracycline (OTC) in different water matrices under simulated sunlight; Fig. 9 This is a comparison chart of the degradation effect of the prepared SCN-E polymer on chlortetracycline (CTC) in different water matrices under simulated sunlight irradiation; Fig.10 The H generation of the prepared CN-E and SCN-E polymers under simulated sunlight 2 O 2 Situation map; Fig.11 The H production of the prepared SCN-E polymer under simulated sunlight 2 O 2 Cyclic degradation diagram; Fig.12 is the XRD pattern of the CN-E and SCN-E polymers in Example 1; Fig.13 1 is the electron paramagnetic resonance spectrum of the CN-E and SCN-E polymers in Example 1. DETAILED DESCRIPTION
[0015] The present invention is described in detail below with reference to specific embodiments. Example 1
[0016] Preparation of S-doped graphitic carbon nitride material with N defects (SCN-E polymer) (1) Preparation of CN-E: 15 g of melamine was calcined at 520 °C in air at a heating rate of 10 °C / min for 4 h, and then calcined again at 580 °C in air at the same heating rate for 4 h to form the original graphite phase carbon nitride CN-E.
[0017] (2) Preparation of SCN-E: 0.4 g of CN-E and 3.5 g of sublimated sulfur powder were added to 50 ml of deionized water, and the mixture was stirred continuously for 1 h in a water bath at 60 °C. After stirring, the mixture should be mixed evenly. The mixture was then heated at 180 °C for 12 h to obtain a yellow solid material. The yellow solid material was then washed alternately with ethanol and water for 3 times, and dried to obtain a light yellow block material. The light yellow block material was calcined at 520 °C in nitrogen at a heating rate of 10 °C / min for 2 h to obtain a light yellow powder material SCN-E polymer, i.e., the S-doped graphite carbon nitride material with N defects.
[0018] Example 2: Photocatalytic degradation of tetracycline antibiotics Take 20 mg of SCN-E polymer from Example 1 and add it to 50 ml of 5 mg·L -1 A 3W LED lamp was used to simulate visible light, and the reaction should be dark for 30 min before illumination to achieve adsorption and desorption equilibrium. The degradation of tetracycline hydrochloride (TC) was analyzed by high performance liquid chromatography. Furthermore, the SCN-E polymer in the system after the first run was saved, and the above operation was repeated in the second run to continue to observe the cyclic degradation activity of the reused SCN-E polymer on the tetracycline hydrochloride solution. 5 mg·L -1 The tetracycline hydrochloride solution was replaced with 10 mg·L -1 Oxytetracycline (OTC) solution and 10 mg·L -1 The photocatalytic degradation and photocatalytic cyclic degradation of oxytetracycline and chlortetracycline by SCN-E polymer were investigated with chlortetracycline (CTC) solution, while other conditions and operations remained unchanged.
[0019] Figure 1 This is a comparison chart of the degradation effects of tetracycline hydrochloride on the best performing SCN-E polymer and pristine graphite phase carbon nitride (CN-E) under simulated sunlight. It can be seen from the figure that in the presence of CN-E, the degradation rate of tetracycline hydrochloride after 30 minutes of illumination is only 65%, while the degradation rate of tetracycline hydrochloride by SCN-E polymer reaches nearly 100%.
[0020] Figure 2This is a comparison chart of the degradation effects of SCN-E polymer with the best performance and original graphite phase carbon nitride (CN-E) on oxytetracycline under simulated sunlight. It can be seen from the figure that in the presence of CN-E, the degradation rate of oxytetracycline after 30 minutes of illumination is only 41.9%, while the degradation rate of SCN-E polymer on oxytetracycline reaches 92.2%.
[0021] Figure 3 This is a comparison chart of the degradation effects of SCN-E polymer with the best performance and original graphite phase carbon nitride (CN-E) on chlortetracycline under simulated sunlight. It can be seen from the figure that in the presence of CN-E, the degradation rate of chlortetracycline after 30 minutes of illumination is only 44.9%, while the degradation rate of chlortetracycline by SCN-E polymer reaches nearly 93.8%.
[0022] Figure 4 This is a cyclic degradation experiment of tetracycline hydrochloride by SCN-E polymer under simulated sunlight irradiation. In the five cyclic degradations, the degradation rates of tetracycline hydrochloride were 100%, 98.52%, 97.36%, 96.57% and 95.59% respectively. This shows that SCN-E polymer has excellent cyclic degradation stability for tetracycline hydrochloride.
[0023] Figure 5 This is a cyclic degradation experiment of SCN-E polymer on oxytetracycline under simulated sunlight. In the five cycles of degradation, the degradation rates of oxytetracycline were 93.8%, 92.1%, 91.5%, 90.8% and 90.1% respectively. This shows that SCN-E polymer has excellent cyclic degradation stability for oxytetracycline.
[0024] Figure 6 This is a cyclic degradation experiment of SCN-E polymer on chlortetracycline under simulated sunlight. In the five cycles of degradation, the degradation rates of chlortetracycline were 93.9%, 93%, 92.5%, 92% and 91.5% respectively. This shows that SCN-E polymer has excellent cyclic degradation stability for chlortetracycline.
[0025] Example 3: Photocatalytic degradation of tetracycline antibiotics in different water matrices Take 20 mg of SCN-E polymer from Example 1 and add it to 50 ml of 5 mg·L -1 The photocatalytic degradation activity of SCN-E polymer on tetracycline hydrochloride solution in different water matrices was tested by HPLC. 5 mg·L -1of tetracycline hydrochloride was replaced with 10 mg·L -1 of oxytetracycline and 10 mg·L -1 The other conditions and operations remained unchanged to investigate the photocatalytic degradation activity of SCN-E polymer towards oxytetracycline and chlortetracycline in different water matrices.
[0026] Figure 7 This is a comparison chart of the degradation effect of SCN-E polymer on tetracycline hydrochloride in different water matrices under simulated sunlight. It can be seen from the figure that the degradation rates of tetracycline hydrochloride in deionized water matrix, tap water matrix, Yellow River water matrix and seawater matrix after 30 minutes of illumination are 100%, 97.2%, 95.6% and 92.5%, respectively, proving that SCN-E polymer has excellent photocatalytic degradation ability of tetracycline hydrochloride in different water matrices and has good anti-interference ability to impurities in different water matrices.
[0027] Figure 8 This is a comparison chart of the degradation effect of SCN-E polymer on oxytetracycline in different water matrices under simulated sunlight. It can be seen from the figure that the degradation rates of oxytetracycline in deionized water matrix, tap water matrix, Yellow River water matrix and seawater matrix after 30 minutes of illumination are 92.2%, 90.1%, 87.5% and 84.2%, respectively, proving that SCN-E polymer has excellent photocatalytic degradation ability of oxytetracycline in different water matrices and has good anti-interference ability to impurities in different water matrices.
[0028] Fig. 9 This is a comparison chart of the degradation effect of SCN-E polymer on chlortetracycline in different water matrices under simulated sunlight. It can be seen from the figure that the degradation rates of chlortetracycline in deionized water matrix, tap water matrix, Yellow River water matrix and seawater matrix after 30 minutes of illumination are 93.8%, 90.2%, 87.7% and 83.3%, respectively, proving that SCN-E polymer has excellent photocatalytic degradation ability of chlortetracycline in different water matrices and has good anti-interference ability to impurities in different water matrices.
[0029] Example 4: Photocatalytic H production 2 O 2 50 mg of SCN-E polymer in Example 1 was added to 50 ml of deionized water solution containing 5% methanol. A 3W LED lamp was used to simulate visible light. The reaction was allowed to proceed in the dark for 30 min before illumination to achieve adsorption and desorption equilibrium. The H 2 O 2Furthermore, the SCN-E polymer in the system after the first run was saved, and the above operation was repeated in the second run to continue observing the effect of the reused SCN-E polymer on H 2 O 2 of photocatalytic cycle to produce activity.
[0030] Fig.10 The H production of CN-E and SCN-E polymers under simulated sunlight 2 O 2 Under light, the H 2 O 2 The yield was 275.16 μmol·L -1 , while the H 2 O 2 The yield was 1183.54 μmol·L -1 The H of SCN-E polymer 2 O 2 The yield is 3 times that of CN-E, which proves that the modified SCN-E polymer can photocatalyze H production. 2 O 2 The performance is better than that of CN-E.
[0031] Fig.11 The H production of SCN-E polymer under simulated sunlight 2 O 2 Cyclic degradation experiment, H production after 5 cycles 2 O 2 In the experiment, 5 times H 2 O 2 The yields were 1183.54 μmol·L -1 、1106.83 μmol·L -1 、1081.83 μmol·L -1 、1025.17 μmol·L -1 % and 996.83 μmol·L -1 This shows that SCN-E polymer has excellent photocatalytic H production 2 O 2 Cyclic stability.
[0032] Fig.12 The XRD patterns of the CN-E and SCN-E polymers in Example 1. The peaks of CN-E correspond to the PDF card (JCPDS-87-1526), 12.8° and 27.8° belong to gC 3 N 4The (100) and (002) planes in the graph correspond to the in-plane and interlayer stacking modes of the conjugated aromatic groups, respectively. The peak type of the SCN-E polymer corresponds to the PDF card (JCPDS-01-83-2285). Compared with CN-E, the diffraction peak of the SCN-E polymer at 12.7° almost disappears, and the doping of surface S reduces the order of its skeleton. And the diffraction peak intensity of the SCN-E polymer at 12.8° is significantly weakened, which may be caused by the high temperature treatment that makes the size of the SCN-E polymer thinner. The diffraction peak of S8 can be seen in the XRD spectrum of the SCN-E polymer, indicating that the surface of the SCN-E polymer is wrapped by sulfur species.
[0033] Fig.13 The electron paramagnetic resonance images of the CN-E and SCN-E polymers in Example 1 show the presence of N defects. The presence of N defects accelerates the interfacial electron transfer rate of the SCN-E polymer, which is beneficial for capturing delocalized electrons, forming a localized state, and improving the separation ability of electron-hole pairs, thereby improving the photocatalytic ability of the SCN-E polymer.
Claims
1. A S-doped graphite carbon nitride material having N defects, characterized in that: The graphite carbon nitride material can photocatalytically degrade tetracycline antibiotic solution on the one hand, and can photocatalytically produce H2O2 on the other hand. The graphite carbon nitride material produces 1183.54 μmol·L -1 of H2O2, within 30 min, 5 mg·L -1 Tetracycline hydrochloride solution, 10 mg·L -1 of oxytetracycline solution and 10 mg·L -1 The degradation rates of chloramphenicol solution reached 100%, 92.2% and 93.8% respectively, and it can be circulated multiple times to efficiently produce H2O2 and degrade tetracycline antibiotics.
2. The method for preparing a S-doped graphite carbon nitride material having N defects according to claim 1, characterized in that: Melamine is calcined at high temperature in air to prepare original graphite carbon nitride, sublimated sulfur powder is added to the original graphite carbon nitride and mixed, and then the S-doped graphite carbon nitride material with N defects is prepared through a hydrothermal method and a secondary calcination method.
3. The method for preparing a S-doped graphite carbon nitride material having N defects according to claim 1, characterized in that: The following steps are involved: (1) Preparation of CN-E: 15 g of melamine was calcined at 520 °C in air at a heating rate of 10 °C / min for 4 h, and then calcined again at 580 °C in air at the same heating rate for 4 h to form the original graphite phase carbon nitride CN-E; (2) Preparation of SCN-E: 0.4 g of CN-E and 3.5 g of sublimated sulfur powder were added to 50 ml of deionized water, and stirred continuously for 1 h in a water bath at 60 °C. After stirring, the mixture should be mixed evenly. Then, it was heated at 180 °C for 12 h to obtain a yellow solid material. The yellow solid material was then washed alternately with ethanol and water for 3 times, and dried to obtain a light yellow block material. The light yellow block material was calcined at 520 °C in nitrogen at a heating rate of 10 °C / min for 2 h to obtain a light yellow powder material SCN-E polymer, i.e., the S-doped graphite carbon nitride material with N defects.
4. A bifunctional photocatalyst prepared by the method of claim 2, wherein a certain amount of the S-doped graphite carbon nitride material having N defects is placed in 50 ml of a tetracycline antibiotic aqueous solution and 50 ml of a methanol aqueous solution, respectively, to achieve photocatalytic degradation of tetracycline antibiotics and photocatalytic production of H2O2.
Citation Information
Patent Citations
Preparation method of carbon / sulfur codoped mesoporous g-C3N4 composite photocatalytic material
CN110227530A
Hollow tubular graphite-phase carbon nitride photocatalyst containing nitrogen defects, preparation method and applications thereof
CN111085238A
Preparation method of g-C3N4 nano sheet photo-catalyst with defects
CN112246272A
Fish scale tubular carbon nitride as well as preparation method and application thereof
CN112892611A
Preparation method and application of nitrogen defect / boron doped tubular carbon nitride photocatalyst
CN113318764A
Cited By
Fe-doped graphite carbon nitride material with N defects as well as preparation method and application of Fe-doped graphite carbon nitride material
CN119857516A
Sulfur-doped / carbon vacancy g-C3N4 with shallow defect state as well as preparation method and application of sulfur-doped / carbon vacancy g-C3N4
CN121423006A